Pollen from the K–Pg boundary of the La Colonia Formation, Patagonia, Argentina - de Benedetti, Facundo; Zamaloa, María C.; Gandolfo, Maria Alejandra; Cúneo, Néstor Rubén (Review of Palaeobotany and Palynology)
The La Colonia Formation, outcropping in northern Chubut Province (Patagonia, Argentina), is a Maastrichtian–Danian sequence deposited during a marine transgression of the South Atlantic Ocean. Its fine-grained sediments are associated with lagoon systems that preserved a very rich and diverse biota composed of invertebrates, vertebrates, plants, algae, and fungi. A palynological study was carried out based on 157 samples collected from four representative stratigraphic sections of this geological unit. The plant communities were dominated in terms of richness by ferns and angiosperms, but algae and gymnosperms were also well-represented. About 250 palynomorphs are recognized. The gymnosperms comprise 20 species including representatives of Araucariaceae, Cheirolepidiaceae, Ephedraceae, and Podocarpaceae while the angiosperms include 67 species within the families Araceae, Arecaceae, Aristolochiaceae, Asteraceae, Cannabaceae, Chlorantaceae, Cunoniaceae, Ericaceae, Gunneraceae, Juncaceae, Liliaceae, Malvaceae, Nelumbonaceae, Nothofagaceae, Proteaceae, and Typhaceae and several taxa of uncertain affinities. Here, we present the systematic study of the gymnosperm and angiosperm pollen components of the flora. Two new gymnosperm species and 22 new angiosperm species are erected. Additionally, we introduce the southernmost records of Triprojectacites and Normapolles groups even though their botanical relationships and origin remain unknown. The highly diverse palynoflora of the La Colonia Formation provides critical evidence for understanding the evolution of Southern Hemisphere floras and of certain clades and families and support the hypothesis that the effect of the mass extinction event was less significant at the southernmost portion of South America than in other parts of Earth. Fil: de Benedetti, Facundo. Museo Paleontológico Egidio Feruglio; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Zamaloa, María C. Museo Paleontológico Egidio Feruglio; Argentina Fil: ...